Tinjauan Hukum Islam Tentang Pembagian Komisi pada Penjualan Rumah : Studi Kasus di PT Propertindo Jaya Selamanya Tahun 2023 - Aulia Fatkhan Qoribah; Alfi Satria; Ali Aminulloh (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The research studies or explores the revenue comission practices on house sale in PT Propertindo Jaya in 2023 from the Islamic law perspective. Regarding Islamic law, the term of ju’alah refers to comission awarded as consideration on services conducted particularly in the context of purchasing media as an agent who assist completing the transaction. The study aims to find out the implementation of comission practices applied and distibuted from the Islamic law point of view. The study uses qualitative approah with descriptive qualitative method. The data are collected throguh the observation, interview and documentation. The data is directly acquired from the related parties with the research object such as the owner of the company, administration and marketing staff as primary sources. And the secondary data sources are books and journals. The study found that the comission or compensation is gradually distributed based on the employee’s performance in sales. The system is in line with the principles or requirements of ju’alah in Islamic law. The company also implements the system of ijarah which means the employees receive monthly salary after performing the duties. And the company shows the obedience towards justice principles and transparency in Islamic muamalah.